(untitled) (Revista Apotheke, 2022)
I built this text as a writing-crossing process created within the incursions in the archives related to my teaching practices in the years 2017, 2018, and 2019 and called teachingarchive. I focused on the subject Laboratory of Artistic Production 1 (LAB1), taught for the fifth grade of the Visual Arts course - Bachelor’s Degree - at the Faculty of Visual Arts (FAV), Federal University of Goiás (UFG). I present the pillars that supported my artistic-pedagogical practice in the mentioned years and highlight the emergence of a telling pedagogy as the primary strategy used to stimulate students’ artistic practice and creative processes in this period. The theoretical references cited point to the fields of narrative research, auto/biographical studies, and decolonial studies. I conclude by recognizing the transforming, critical, and liberating aspects of the acts of creation within the university environment. They are capable of undoing and remaking connections with our subjectivities, moving us to other places from where we can perceive new ways of doing, thinking, and existing in art, education, and life.